Brain calcifications and PCDH12 variants. (August 2017) - Nicolas, Gaël; Sanchez-Contreras, Monica; Ramos, Eliana Marisa; Lemos, Roberta R.; Ferreira, Joana; Moura, Denis; Sobrido, Maria J.; Richard, Anne-Claire; Lopez, Alma Rosa; Legati, Andrea; Deleuze, Jean-François; Boland, Anne; et al.
Abstract : Objective: To assess the potential connection between PCDH12 and brain calcifications in a patient carrying a homozygous nonsense variant in PCDH12 and in adult patients with brain calcifications. Methods: We performed a CT scan in 1 child with a homozygous PCDH12 nonsense variant. We screened DNA samples from 53 patients with primary familial brain calcification (PFBC) and 26 patients with brain calcification of unknown cause (BCUC). Results: We identified brain calcifications in subcortical and perithalamic regions in the patient with a homozygous PCDH12 nonsense variant. The calcification pattern was different from what has been observed in PFBC and more similar to what is described in in utero infections. In patients with PFBC or BCUC, we found no protein-truncating variant and 3 rare (minor allele frequency <0.001) PCDH12 predicted damaging missense heterozygous variants in 3 unrelated patients, albeit with no segregation data available. Conclusions: Brain calcifications should be added to the phenotypic spectrum associated with PCDH12 biallelic loss of function, in the context of severe cerebral developmental abnormalities. A putative role for PCDH12 variants remains to be determined in PFBC.